First Time Synthesis, Characterization And Synergistic Photocatalytic Effect Of GO/Bi2O3/Nb2O5 Nanocomposites. (2018) - Ghorai, Tanmay K; Sikdar, Suranjan; Das, Subhapriya; Pathak, Sayantan; Pattanayak, Sutanuka; Biswas, Niladri
Abstract: Nanocomposites of metal oxide show unique and enhanced properties in optical, magnetic, catalytic and electrical fields. Particularly, Nanocomposites of Graphene oxide (GO)) /Bi2 O3 /Nb2 O5 shows very good photocatalytic activity for reduction of 4-nitrophenol (4-NP) and 4-nitroaniline (4-NA) in presence of sunlight. Novel nanocomposites of GO/Bi2 O3 /Nb2 O5, GO/Bi2 O3 and GO/Nb2 O5 are synthesized by either adopting ball-milling or solid state method. The rapid photo reduction of 4-NP to 4-aminophenol (4-AmP) and 4-NA to 4-phenylenediamine (4-PDA) by the use of sodium borohydride (NaBH4 ) in aqueous solution is selected as a model reaction to investigate the photocatalytic activity of GO/Bi2 O3 /Nb2 O5 nanocomposite. It is found that GO/Bi2 O3 /Nb2 O5 nanocomposite has better reduction efficiency (96%) on 4-NP and 4-NA in presence of sunlight rather than in absence of sunlight compared the other GO or GO/Bi2 O3 or GO/Nb2 O5 nanocomposites. The crystallite sizes and grain sizes of GO/Bi2 O3 /Nb2 O5 are 64±1 and 70±2 nm with specific cubic shape. The FT-IR clearly reveals that GO, Bi and Nb are well incorporated in the GO/Bi2 O3 /Nb2 O5 composition.